Linguistic and Cultural Interactions between Greece and the Ancient Near East
1 online resource.
Keywords: The aim of this book is to provide new insights on the multi-faceted topic of the relationships between ancient Greece and ancient Anatolia before the Classical era. This is a rapidly evolving field of enquiry, thanks to the recent advances in our understanding of the Anatolian languages and the ever-growing availability of primary evidence. The chapters in this volume investigate the question of Graeco-Anatolian contacts from various points of view and with a specifically linguistic and textual focus. The nature of the evidence calls for an interdisciplinary approach, and the contributions presented here range from writing systems to contact linguistics, without excluding the analysis of cultural motifs and religious practices in both literary texts and non-literary evidence.